Indonesian Muslim Tradition during COVID-19 Pandemic - Aditya Kusumawati (Universitas Airlangga, 2022)
Background: The majority of Indonesians are Muslim (87%) scattered in each province. They celebrated Eid al-Fitr at the end of May 2020 along with the COVID-19 pandemic that has not ended yet. The tradition of celebrating Eid day is contradictive to the COVID-19 transmission prevention efforts that prohibit people from the crowd, prohibit having activities outside of their houses, and limit human mobilization. Even the president has imposed a ban on mudik Lebaran (coming back to hometown) due to the prediction of massive human migration. The handling of the COVID-19 pandemic requires participation of all parties, including the central government, regional governments, local leaders, the private sector, and the whole community. Objective: This study aims to describe the Indonesian Muslim tradition related to the prevention of the transmission of COVID-19 pandemic. Methods: This was quantitative research with a cross-sectional design. Data were collected a day before Eid day. There were 246 Muslims in Central Java province as respondents. Variables in this study were respondent characteristics (age, sex, educational level, occupation, and economic level) and Muslim Eid Al-Fitr tradition such as mudik tradition, Eid shopping needs, silaturahmi tradition, and Eid praying. This study also identified the respondents' practice in preventing COVID-19 transmission. All variables were analyzed descriptively to explain how Muslims conducted their tradition during the COVID-19 pandemic. Results: COVID-19 pandemic caused most Muslims not to celebrate Eid as usual. They had to be far away from their families. On the other hand, the tradition to visit the tombs of the ancestors was also maintained by Javanese people and had become a habitual culture. Carelessness and disobedience against health protocols during a pandemic might bring fatal consequences to themselves and others. Conclusion: Most Muslims were discouraged from mudik, silaturahmi, and performing Eid prayer in a congregation in the mosque. They encountered difficulties to keep physical distancing due to people around did not exercise physical distancing for themselves.